Understanding coupling in the context of an SOA promoting protocol-based integration. - Linthicum, David
As we bring our SOAs online using Web Services, we all know that SOAP is the standards message transfer protocol. But the interface description language for Web Services (WSDL) isn't specifically for SOAP. It's more generic. A SOAP-centric contract description language for Web Services is needed. Enter the SOAP Service Description Language or SSDL. This framework was just released in mid-February and is now available for review.